Geschichtsarbeit in einem Zwischenraum. Das Zentrum für Ostbelgische Geschichte - Lejeune, Carlo („Mit Belgien ist das so eine Sache ...“ Resultate und Perspektiven der Historischen Belgienforschung, 2021)
Keywords: Geschichtsschreibung; Ostbelgien

Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

Ein Schattendasein in der Geschichtsschreibung. Wenige Blicke auf die Zwischenräume im langen 19. Jahrhundert - Brüll, Christoph; Lejeune, Carlo; Lejeune, Carlo (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Geschichtsbild; Geschichtsschreibung; Ostbelgien

„Den Gefallenen der beiden Weltkriege“. Eupen und seine Weltkriegstoten - Brüll, Christoph; Mießen, Werner (Liber Amicorum Alfred Minke, 2011)
Keywords: Erster Weltkrieg; Eupen; Gedenktag; Geschichtsbild; Geschichtspolitik; Geschichtsschreibung; Kollektives Gedächtnis; Zweiter Weltkrieg

Vergangenheitsbewältigung und Zukunftsgestaltung im ostbelgischen Grenzland - Bergmans, Bernhard (Im Göhltal, 2009)
Keywords: Geschichtsbild; Geschichtsschreibung